Linking two worlds in polymer chemistry: The influence of block uniformity and dispersity in amphiphilic block copolypeptoids on their self‐assembly. Issue 4 (7th February 2019) - Gangloff, Niklas; Höferth, Marcel; Stepanenko, Vladimir; Sochor, Benedikt; Schummer, Bernhard; Nickel, Joachim; Walles, Heike; Hanke, Randolf; Würthner, Frank; Zuckermann, Ronald N.; Luxenhofer, Robert
Abstract: The self‐assembly of block copolymers has captured the interest of scientists for many decades because it can induce ordered structures and help to imitate complex structures found in nature. In contrast to proteins, nature's most functional hierarchical structures, conventional polymers are disperse in their length distribution. Here, we synthesized hydrophilic and hydrophobic polypeptoids via solid‐phase synthesis (uniform) and ring‐opening polymerization (disperse). Differential scanning calorimetry measurements showed that the uniform hydrophobic peptoids converge to a maximum of the melting temperature at a much lower chain length than their disperse analogs, showing that not only the chain length but also the dispersity has a considerable impact on the thermal properties of those homopolymers. These homopolymers were then coupled to yield amphiphilic block copolypeptoids. SAXS and AFM measurements confirm that the dispersity plays a major role in microphase separation of these macromolecules, and it appears that uniform hydrophobic blocks form more ordered structures. Abstract :